Distribution of Preeclampsia Risk Factors in Pregnant Woman with Mild Preeclampsia in Banyumas District - Diki Retno Yuliani; Suharyo Hadisaputro; Sri Achadi Nugraheni (JURNAL KEBIDANAN, 2019)
Preeclampsia became the dominant cause of maternal death in Banyumas district in 2018, as an effort to prevent preeclampsia is by carrying out early detection of preeclampsia risk factors. The purpose of this study was to know the description of preeclampsia risk factors in Banyumas District. The research design was quantitative descriptive research. The sample was 32 pregnant women with mild preeclampsia with cluster sampling technique. Data collection using questionnaires by filling in through interviews and data analysis using frequency distribution. The results showed the three most risk factors were interbirth interval 10 years (46.9%), history of preeclampsia/hypertension (43.7%), and obesity (28.1%). While the three least risk factors were twin pregnancies (3.1%), a history of diabetes mellitus (6.3%), and a family history of preeclampsia (9.4%). The majority of respondents had preeclampsia risk factors (90.6%), the highest number were 2 risk factors (43.8%), and 9.4% did not have risk factor. The conclusion of this study was that the majority of respondents have risk factors for preeclampsia, so the identification of preeclampsia risk factors is still relevant to be used as an effort to prevent preeclampsia.